Don't panic! Cultural difficulties in the translation of English humour into Spanish for a Cuban context: The hitchhiker's guide to the galaxy - Jordan Enriquez, Rosa Margarita (2018)
In Cuba, the literary translation of humour in works of science fiction or fantasy rarely occurs, so readers must turn to foreign editions that have a different cultural background and therefore a different sense of humour. That is why this study focuses on the need of translating English humour for a Cuban context. The hypothesis is that English humour presents culture-bound elements unintelligible for a Cuban audience and that a combination of translation strategies and extensive knowledge of the two cultures is the key for its successful translation. The aim of this research is to identify the main obstacles for the intercultural translation of English humour and the strategies to recreate it in a Cuban context. This research includes an exploration of both humour variants and a case analysis of culture-bound jokes from the novel The Hitchhiker’s Guide to the Galaxy. The cultural problems identified include culture-specific concepts, intertextuality, slang, and understatement. The most efficient strategies to solve them were cultural substitution, explicitation and loan words. The present study can raise intercultural awareness and highlight the key role of translators as cultural mediators.